Individual Variation in Movement Behavior of Stream-Resident Mediterranean Brown Trout (Salmo trutta Complex) - Enric Aparicio; Rafel Rocaspana; Antoni Palau-Ibars; Neus Oromí; Dolors Vinyoles; Carles Alcaraz (Fishes)
Understanding individual movement patterns in stream-resident salmonids is critical for conservation and river management, particularly in Mediterranean streams characterized by high environmental variability. We tagged 997 Mediterranean brown trout (Salmo trutta complex) and conducted an 11-month mark–recapture study using Passive Integrated Transponder (PIT) technology to assess movement behavior in the Flamisell River (Ebro Basin, northeastern Iberian Peninsula). Movements followed a leptokurtic distribution, with 81.8% of the individuals classified as sedentary (median movement = 24.9 m) and 18.2% as mobile (median movement = 376.2 m). Generalized linear models revealed distinct drivers of fish movement for each group. In sedentary trout, movement was mainly influenced by mesohabitat type, season, sex, and body size, with males and larger individuals moving farther. In mobile trout, mesohabitat type, density, and body size were key predictors. Movement patterns were repeatable over time, indicating consistent behavioral tendencies. These results support a bimodal movement strategy and highlight the importance of individual variation. Conservation planning should account for both sedentary and mobile groups to preserve functional and genetic connectivity and improve resilience of Mediterranean streams.